From Incremental to Exponential - Amla, Ismail (Berrett-Koehler Publishers, 2020)
"This timely book reminds us that innovation is agnostic about where it's created." />'Satya Nadella, CEO, Microsoft /> />Over and over, we see big legacy businesses getting beaten to the punch by energetic little start-ups. It seems like innovation can come from only the bottom up or from the outside in. But tech experts Vivek Wadwha and Ismail Amla are here to tell you that "big equals slow and stodgy" is a myth. Based on decades of experience working with both the world's leading brands and disruptive start-ups, this book explores the opportunity legacy companies have to create new markets, supercharge growth, and remake their businesses by combining the mindset and tool belt of start-ups with the benefits of incumbency: boatloads of customer data, decades of brand equity, robust distribution channels, enormous financial assets, and more. /> />Wadhwa and Amla go deeply into why the pace and dynamics of innovation have changed so dramatically in recent years and show how companies can overcome obstacles like the Eight Deadly Sins of Stasis. Equally important, they provide a playbook on how to use their insights in your own company, team, or career. This fast-paced, anecdote-rich story rethinks modern innovation'a book every manager, executive, and ambitious employee will want to read. />
Title from content provider
Keywords: Business; Affaires; BUSINESS & ECONOMICS; Decision-Making & Problem Solving